Pengaruh Pelatihan Kecerdasan Spiritual terhadap Tingkat Kecemasan Mahasiswa yang Sedang Mengerjakan Skripsi - Karina Intan Harsupadni; Mira Aliza Rachmawati (Universitas Islam Indonesia, 2009)
Ttiis experiment examined the influence of spiritual intelligence training on student college anxiety that enrolls undergraduate studies. The hypothesis was that there is a significant anxiety level difference between experimental and control group.The subjects of this experiment were Student College with age ranging from 22 26 years old. The design of this experiment was Pretest Posttest with Control Group Design. A measure of student anxiety was developed by using aspects from Nevid (2003). The training module was developed on the basis of Emmons Theory (Hendrawati, 2004).Data were analyzed using gain score method. The result show that there is an anxiety level difference between experimental and control group ff =- 3,732. p = 0,003, p<0,05). 77ms means that the spiritual intelligence training show influence in decreasing student anxiety. An experiment group data analysis show that there is an anxiety difference prior and after the training (t=-16.819; p<0.01). The result of this experiment confirmed the hypothesis.Keyword: spiritual intelligence training, anxiety